1954
DOI: 10.1021/jf60036a007
|View full text |Cite
|
Sign up to set email alerts
|

Residue Analysis, Direct Potentiometric Method for Chloride Ion Applied to Residues of Chlorinated Insecticides

Abstract: The quantitative determination of chlorinated-insecticide residues in treated foodstuffs by total chlorine methods is expedited and simplified by the exploitation of an unusually sensitive direct potentiometric method for chloride ion. This method uses a pH meter and a silver-silver chloride vs. calomel electrode system, and responds reproducibly to as little as 0.02 p.p.m. of chloride ion. With the equipment and procedures recommended, the useful range, without concentration or dilution stages, appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1958
1958
1972
1972

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Other Factors. As discussed by Helmkamp et al (6) and as mentioned earlier, certain inorganic ions interfere in this method. Also, precision temperature control at the sensor electrode is essential by virtue of the Nernst equation.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Other Factors. As discussed by Helmkamp et al (6) and as mentioned earlier, certain inorganic ions interfere in this method. Also, precision temperature control at the sensor electrode is essential by virtue of the Nernst equation.…”
Section: Resultsmentioning
confidence: 75%
“…to approximately 0.01 p.p.m. One total organic chloride method (4,6) consists of producing hydrogen chloride gas by combustion, trapping this gas in a dilute solution of sodium carbonate-containing chloridefree nitric acid to suppress the ultimately interfering (4,6) carbonate ion, and measuring the chloride ion concentration by simple direct potentiometry with a silver-silver chloride vs. slow leak calomel electrode system. Amounts of original insecticides are then calculated from their percentage Mack, and Childs and the pathway suggested in the present study is the principal rate-determining step reported here.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The potentiometric determination of chloride has been studied with a concentration cell employing two silver-silver chloride electrodes (S, 11,24). A simpler and more direct potentiometric measurement of chloride has been the object of recent investigations (5,14,16). Chanin (5) used a cell with a silver-silver chloride indicator electrode and a mercury-mercurous sulfate reference electrode.…”
mentioning
confidence: 99%